2011
DOI: 10.1152/ajpendo.00233.2011
|View full text |Cite
|
Sign up to set email alerts
|

Developmental exposure to di(2-ethylhexyl) phthalate impairs endocrine pancreas and leads to long-term adverse effects on glucose homeostasis in the rat

Abstract: -Di(2-ethylhexyl) phthalate (DEHP), a typical endocrine-disrupting chemical (EDC), is widely used as plasticizer. DEHP exposure in humans is virtually ubiquitous, and those undergoing certain medical procedures can be especially high. In this study, we investigated whether developmental DEHP exposure disrupted glucose homeostasis in the rat and whether this was associated with the early impairment in endocrine pancreas. Pregnant Wistar rats were administered DEHP (1.25 and 6.25 mg·kg(-1)·day(-1)) or corn oil t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
90
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(100 citation statements)
references
References 38 publications
(35 reference statements)
8
90
1
1
Order By: Relevance
“…Studies in sheep have shown that prenatal exposure to testosterone is associated with lower birth weight, developmental changes in insulin-like growth factor (IGF)/IGF binding protein system, and insulin resistance (reviewed in [50]). In a recent study in which rats were developmentally exposed to the suspected androgen DEHP, female rats were observed to have impaired glucose tolerance and insulin secretion [51]. Male rats showed increased serum insulin levels, and both female and male rats had a significantly lower birth weight than controls.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in sheep have shown that prenatal exposure to testosterone is associated with lower birth weight, developmental changes in insulin-like growth factor (IGF)/IGF binding protein system, and insulin resistance (reviewed in [50]). In a recent study in which rats were developmentally exposed to the suspected androgen DEHP, female rats were observed to have impaired glucose tolerance and insulin secretion [51]. Male rats showed increased serum insulin levels, and both female and male rats had a significantly lower birth weight than controls.…”
Section: Discussionmentioning
confidence: 99%
“…As an endocrine disruptor, DEHP altered male sexual differentiation [7] and disturbed energy metabolism in animals [[8],[9]]. Investigations mainly focused on the potential adverse effects of DEHP and MEHP, its active metabolite, on the reproductive system, carcinogenicity, liver, kidney and developmental toxicities [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, DEHP is an endocrine disruptor that is able to alter sexual differentiation and energy metabolism (10)(11)(12). Given its chemical structure, DEHP easily enters food, air and even the human body.…”
Section: Discussionmentioning
confidence: 99%
“…Di-(2-ethylhexyl) phthalate (DEHP) is the most common environmental endocrine disruptor (10)(11)(12). DEHP is widely used in consumer products, including food packaging, medical devices and toys, to improve the flexibility and durability of polyvinyl chloride-based plastics.…”
Section: Introductionmentioning
confidence: 99%